Arc bead ignition of a cellulose fuel bed derived from experimental and simulated data. (1st May 2023) - Lyu, Hui-Fei; Wang, Cai-Ping; Deng, Jun; Wang, Wei-Feng; Li, Yang; Shu, Chi-Min
Graphical abstract: Highlights: The ignition phenomenon of cellulose by electrical faults beads was investigated. The ignition behaviors were determined from the experiments. The numerical model was developed to predict the ignition characteristics. The model described the mechanism of the ignition phenomenon reasonably well. Abstract: Cellulose is the most abundant material and widely used fuel in the world, and on the other hand, it is also the risk of forest potential fire hazards. Fires caused by electrical arc beads, which are detrimental to the environment, occur in wildland-urban interface (WUI) areas. This study experimentally and numerically examined the ignition behavior of the cellulose fuel bed by focusing on arc beads. Experiments were conducted using authentic arc fault beads, and the effects of the bead temperature and implantation depth on ignition phenomena were investigated. Three ignition categories were determined: no, smoldering, and flaming ignition. Ignition temperature limits were determined by performing a statistical analysis, and experimental observations were used to develop a mathematical model. The two-step reaction leading to cellulose ignition was discussed, and natural convection, diffusion, and thermal radiation were all identified as influential parameters. Four ignition mechanisms were identified using the model: no ignition, smoldering or charring inside the fuel bed, smoldering leading to volatiles ignited, and flaming ignition. The ignition phenomenon was limited by the conduction and accumulation of heat, presence of volatile substances, and concentration of atmospheric oxygen. The model reasonably predicted the ignition phenomenon and described the ignition mechanism. These results can be used to reduce the risk of fire hazards related to arc beads, particularly in WUI areas.